A 10 years Trend of Peptic Ulcer Disease and other Gastrointestinal Disorders in Northern Uganda - Okello, T.R.; Ogwang, D.M; Pecorella, I. (East and Central African Journal of Surgery, 2016)
The changing trend of GI disorders has not been expounded in our setting, there is need to examine the extent to which major endoscopically diagnosed upper GI disorders have changed in the last 10 years (2005 to 2015). Methods: This was a retrospective study in which endoscopically diagnosed GI disorders of Jan-Jun 2005 were compared with 2015 (10 years) for the same period Results: In the 10 years (2005 to 2015), the prevalence of peptic ulcer disease (PUD) reduced from 9.6% to 2.9% (P value 0.000), followed by esophageal varices from 10.3% to 4.0%, and duodenitis from 3.2% to 0.7% respectively. Gastritis increased from 18.4% to 48.2% (P value 0.000), followed by cancer esophagus from 3.2% to 5.1%. Conclusion: As the prevalence of PUD decreases in our community, gastritis increases hence patients with upper GI symptoms tend to suffer gastritis thus clinicians should focus on treating gastritis and eradication of Helicobacter pylori.
Keywords: Peptic ulcer disease; Gastritis; GI Disorders